Photonic millimeter-wave bridge for multi-Gbps passive optical networks - Aldaya, Ivan [UNESP]; Del-Valle-Soto, Carolina; Campuzano, Gabriel; Giacoumidis, Elias; Gonzalez, Rafael; Castanon, Gerardo (Elsevier B.V., 2018)
Survivability is a critical requirement of optical communication networks that is typically addressed implementing path diversity. However, due to the elevated cost of fiber installation, this approach may prove prohibitively expensive in optical access networks. In this paper, a novel cost-efficient photonic millimeter (mm)-wave bridge is proposed, which converts passive optical network (PON) signals to radiofrequency signals at mm-wave bands. The performance of the mm-wave photonic bridge is numerically tested, revealing its feasibility to transmit a 2.5-Gbps PON with -55.6 dB wireless link gain (WLG) using the 81-86 GHz band and 10-Gbps PON with -35 dB at the 102-109.5 GHz band. The effect of fiber is also analyzed, showing that fiber cuts closer to the optical network unit degrades more the system performance. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Passive optical networks; mm-wave links; Network survivability